Early-Age Behaviour of Post-Tensioned Low-CO2 and Fibre-Reinforced Concrete - An Experimental Study Using Distributed Optical Fibre Sensing - Bruhn, Elisabeth; Durling, Stina (My University, 2026)
The construction industry is under increasing pressure to reduce its environmental im pact, driving the development of low-carbon concrete solutions. In parallel, prestressed concrete systems provide opportunities for improved material efficiency, while the in clusion of fibre-reinforced concrete in forthcoming Eurocode provisions promotes hy brid reinforcement strategies aimed at enhancing structural performance at the service ability limit state. Utilizing distributed optical fibre sensing (DOFS) could help optimize structural designs. Thecombined use of climate-improvedconcrete, fibre reinforcement, and post-tensioning still lacks comprehensive experimental validation. This study addresses this gap through an experimental investigation of the static and long-term behaviour of post-tensioned concrete beams with different concrete compositions. Particular focus is placed on time-dependent effects such as creep, shrinkage, and relaxation, analysed using DOFS and compared with analytical predictions according to Eurocode 2. Three beam specimens were tested: a conventional reference beam, a low-CO2 con crete beam, and a fibre-reinforced low-CO2 concrete beam. All beams were cast using self-compacting concrete, where part of the Portland cement was replaced with ground granulated blast-furnace slag in the low-CO2 mixes. The results show consistent structural behaviour with expected prestress losses and de formation patterns. The low-CO2 and fibre-reinforced concretes exhibited smaller long term deformations than the conventional concrete, indicating reduced creep behaviour. In addition, the DOFS system accurately captured both the strain development and the overall structural response during tensioning and long-term monitoring. The findings indicate that reduced cement content can provide comparable or improved structural performance when time-dependent behaviour is considered. Furthermore, the analytical predictions according to Eurocode 2 tended to overestimate the long term prestress losses compared with the experimental observations, highlighting the conservative nature of the code-based approach.
Keywords: Low CO2-concrete, Fibre-reinforced concrete, Post-tension, Distributed Optical Fibre Sensing (DOFS), Prestress losses, Creep, Shrinkage, Relaxation